Prosedur Pengurusan Dokumen Keberangkatan Kapal pada Kantor KSOP Kelas I Dumai oleh PT. Tarunacipta Kencana Cabang Dumai - Fernanda Aulia; Syarifur Ridho; Yuna Sutria (Universitas 17 Agustus 1945 Semarang, 2024)
This paper explains the procedures for processing ship departure documents. PT. Tarunacipta Kencana Dumai Branch as a shipping company that handles ships entering and exiting Dumai Port and completes ship documents before the ship leaves Dumai Port. During the land practice, the author collected data using field research methods and library research methods, articles and journals related to the title and other supporting media. Procedures for processing ship departure documents have been effective and efficient. PT. Tarunacipta Kencana Dumai Branch as an agent who handles all ship departure documents for the relevant agencies starting from arranging Port Health Quarantine Clearance (PHQC) at the Quarantine office, processing Out Passport permits at the Immigration office, Crew List Out at the Port Authority office, Outward Manifest at the Customs and Excise office until the issuance of the Sailing Approval Letter (SPB) at the Harbormaster's office.